2019
DOI: 10.7150/jca.31243
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Signature in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers in the world. Circular RNAs (circRNAs) are a new class of endogenous functional non-coding RNAs (ncRNAs), and have been demonstrated to play important roles in the development of HCC. This study aimed to explore the significance of circRNAs in HCC progression. HCC-associated circRNA expression profiles GSE94508 and GSE97332 were downloaded from the Gene Expression Omnibus database (GEO), and 87 differentially expressed circRNAs (DECs) between HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 57 publications
4
61
0
Order By: Relevance
“…hsa_circ_0003645 was previously identi ed to be upregulated in non-small cell lung cancer tissue [27]. hsa_circ_0038718 was reported to be upregulated in hepatocellular carcinoma [28]. Our result suggested that hsa_circ_0003645 and hsa_circ_0038718 may also play an oncogenic role as a sponge of hsa-miR-139-3p.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…hsa_circ_0003645 was previously identi ed to be upregulated in non-small cell lung cancer tissue [27]. hsa_circ_0038718 was reported to be upregulated in hepatocellular carcinoma [28]. Our result suggested that hsa_circ_0003645 and hsa_circ_0038718 may also play an oncogenic role as a sponge of hsa-miR-139-3p.…”
Section: Discussionsupporting
confidence: 52%
“…The function of hsa_circ_0001917 in PTC has not been reported. However, hsa_circ_0001917 was also identi ed to be upregulated in hepatocellular carcinoma [28]. Our result suggested that the upregulated hsa_circ_0001917 may sponge hsa-miR-139-5p, promoting PTC via upregulation of RIMS2.…”
Section: Discussionmentioning
confidence: 69%
“…Circular RNAs (circRNAs) are a type of naturally occurring RNAs which are synthesized by "head to tail" splicing of coding or non-coding RNAs (ncRNAs) [4]. circRNAs were identified to be important regulators in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that circRNAs are involved in various human diseases, particularly cancers [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%